Orientação para planejamento de atividade de campo: contribuições de P. Ya. Galperin - MENDONÇA, Remir Alencar (2018)
The present work addresses a proposal of orientation for planning a field activity based on the Theory of Assimilation by Mental Stages and Formation of Concepts of Galperin. This theory is based on the ideas of Vigotsky and Leontiev, therefore with developmental characteristics. As well as bringing ideals of socialism influenced by Karl Marx, by the ideas of orientation, Leontiev by the concept of the ideal; Vigotsky by the conception of the activity, by V. Lenin (the main forms of psychic reflex). The study presents a discussion about the importance of guidance as the basis for quality learning. It also points out that the importance of field lessons as a didactic tool that motivates and approaches the student of knowledge and as a facilitator for those who have difficulty learning through conventional means, enabling the sharing of knowledge at all levels. As a suggestion will be presented a didactic proposal for the planning of field activities according to Theory of Mental Assimilation by Stages and Formation of Concepts.